A Systematic Review of the Impact of Patient and Public Involvement on Service Users, Researchers and Communities - Brett, Jo; Staniszewska, Sophie; Mockford, Carole; Herron-Marx, Sandra; Hughes, John; Tysall, Colin; Suleman, Rashida (The patient : patient-centered outcomes research, 2014)
Objective Patient and public involvement (PPI) in research has expanded nationally and internationally over the last decade, and recently there has been significant attention given to understanding its impact on research. Less attention has been given to the impact of PPI on the people involved, yet it has been shown that the success of PPI in research can be reliant on the processes of engagement between these individuals and communities. This paper therefore critically explores the impact of PPI on service users, researchers and communities involved in health and social care research. Data Sources Searches were undertaken from 1995 to April 2012 in the electronic databases MEDLINE, EMBASE, PsycINFO, Cochrane library, CINAHL, HMIC and HELMIS. Searches were undertaken for grey literature using the databases InvoNet and NHS Evidence. Study Selection Studies were included if they included the impact of PPI on individual service users, researchers or communities under research. Studies were excluded if they were in a foreign language (unless they were deemed critical to the systematic review) or were in children and adolescent services. Study Appraisal Data were extracted using a narrative synthesis, and quality was assessed using the Critical Appraisal Skills Programme. Main Results Service users reported feeling empowered and valued, gaining confidence and life skills. Researchers developed a greater understanding and insight into their research area, gaining respect and a good rapport with the community. The community involved in research became more aware and knowledgeable about their condition. However, lack of preparation and training led some service users to feel unable to contribute to the research, while other service users and communities reported feeling overburdened with the work involved. Researchers reported difficulties in incorporating PPI in meaningful ways due to lack of money and time. Conclusion This is the first international systematic review to focus on the impact of PPI on the people involved in the process. The beneficial and challenging impacts reported highlight the importance of optimising the context and processes of involvement, so creating the potential for PPI to impact positively on the research itself.